A WAR WITHOUT INFLATION: THE CASE OF ARGENTINA 1865–1870. (December 2022) - Newland, Carlos
ABSTRACT: Although paper note issuance increased dramatically in Argentina during the Triple Alliance War, inflation was not significant. This occurred because only a fraction of the increase in paper bills led to an expansion of the money supply, the rest being currency substitution. On the other hand, an increase in the demand for money for transactions was generated by rapid economic growth.